2016
DOI: 10.1039/c6ra04956g
|View full text |Cite
|
Sign up to set email alerts
|

Wollastonite ceramics with bimodal porous structures prepared by sol–gel and SPS techniques

Abstract: In this work we suggest a novel synthetic route combining Sol-Gel and SPS to fabrication of porous ceramics based on wollastonite with bimodal pore size distribution (100-500 nm and 1-500 µm) and high mechanical strength (Young's Modulus from 72.5 to 172 MPa). We studied peculiarities of formation biporous silicate framework using two types of poreforming additives (templates) of various nature, shape and size, introduced during different stages of Sol-Gel and SPS synthesis: organo-nonorganic (polymer latex of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…(i) The first one, which is generally utilized due its reliability, implies the use of inorganic synthesis by different methods, such as hydrothermal [20,21], co-precipitation [22,23], or sol-gel [24]. However, these approaches are, on one hand, polluting and time-consuming, and, on the other hand, quite expensive [25,26].…”
Section: Bioha Vs Synthetic Hamentioning
confidence: 99%
“…(i) The first one, which is generally utilized due its reliability, implies the use of inorganic synthesis by different methods, such as hydrothermal [20,21], co-precipitation [22,23], or sol-gel [24]. However, these approaches are, on one hand, polluting and time-consuming, and, on the other hand, quite expensive [25,26].…”
Section: Bioha Vs Synthetic Hamentioning
confidence: 99%
“…In order to solve the problems in the synthesis of CaSiO 3 biocomposite ceramics, including those reinforced with HAp, the approaches using an unconventional technique of spark plasma sintering (SPS, widely studied in [18][19][20]), and reactive SPS, as well as combinations of this technique with sol-gel and template syntheses, have been considered and implemented. As a result, micro-and nanostructured CaSiO 3 bioceramics with a macroporous [21,22] and bimodal ordered structure [23], with doped nanosized gold [24], reinforced with HAp [25,26], which have biocompatible properties, relatively high mechanical characteristics, and a defect-free porous framework have been successfully obtained and studied.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown the effectiveness of using wollastonite (calcium monosilicate Ca 6 Si 6 O 18 with a theoretical composition, wt.%: CaO—48.3, SiO 2 —51.7 [ 25 , 26 , 27 , 28 , 29 ]) to increase the strength and durability of PCM [ 30 , 31 , 32 , 33 , 34 ]. Wollastonite is used in various high-tech fields including the ceramics and polymer industry [ 35 , 36 , 37 , 38 ]. The use of wollastonite as a filler in PCM is associated with its reinforcing effect on the polymer matrix, chemical inertness, high melting point, and environmental friendliness [ 38 ].…”
Section: Introductionmentioning
confidence: 99%